DIABETIC RETINOPATHY AND RETINAL VASCULAR DISEASES - Laura Khachatrian (Modern American Journals, 2025)
According to WHO, the number of people living with diabetes has increased from 200 to 830 million in the past thirty-five years (since 1990). In 2020, more than a million people became blind due to diabetic retinopathy (DR), and almost 3.28 million suffered from moderate to severe visual impairment (MSI). DR is recognized as one of the most common causes of blindness and visual impairment among the working-age population worldwide. At the same time, early detection and treatment of MVI can reduce the risk of severe vision loss by approximately 90 percent.
Keywords: Diabetic retinopathy, diabetes mellitus (DM), hyperglycemia, diabetic macular edema (DME), blood-retinal barrier (BRB), VEGF, cytokines, chemokines, angiopoietin-2, panretinal photocoagulation.